Adaptive Network-Based Fuzzy Inference System Modeling Of CO2 Laser Cutting Performance - Subramonian, Sivarao (2011)
The main aim of this research was to construct an Adaptive Network-based Fuzzy Inference System (ANFIS) framework which is fuzzy inference system with hybrid learning strategy combining gradient descent and Kalman filter algorithm which is very appropriate for non-linear process modeling, time series prediction and intelligent control.